Movable Page-Based Interactive Books on Numbers in Elementary Schools - Vina Amilia Suganda M; Laihat Laihat; Bunda Harini; Mazda Leva Okta Safitri; Sendy Putri Melati; Dhimas Rahmadan; Suci Hayati; Ciptro Handrianto (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2023)
The development of a Movable Page-Based Interactive Book on Numbers in Elementary Schools aims to determine the feasibility and effectiveness of the product being developed. The use of teaching materials has an important role including the role for students, teachers in classical learning, groups and individuals. An interactive book based on Movable Pages is a teaching material that is systematically arranged to help students understand the concept of numbers in elementary schools. This study uses a development research approach by applying the ADDIE Model (Analyze, Design, Development, Implementation, Evaluation). Research that has been carried out up to the Development stage. Based on the results of the research that the development of movable page-based interactive books on number material of n elementary schools was developed declared and valid by 4 (four) validators, with a percentage of 90.4% in the very valid cate-gory. In the implementation stage, namely the product trial stage, namely one-to-one and small group trials which were carried out in class V students at SD Negeri 11 Sungai Pinang as many as 21 students, the results of the student questionnaire recapitulation were 89.7% with the very good category. Thus, from the several stages that have been passed in this study, it was found that the Movable Page-Based Interactive Book on Numbers Material in Elementary Schools is valid and practical. This interactive book can help elementary school teachers so that students can easily understand number material in learning mathematics and fur-ther researchers can continue this research to determine the effectiveness of interactive book products and can develop interactive books for other materials in learning mathematics in elementary schools.